2019
DOI: 10.1097/md.0000000000016808
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nephrology referrals and multidisciplinary care programs on renal replacement and medical costs on patients with advanced chronic kidney disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Regarding secondary outcome indicators, two studies reported that MDC significantly decreased the emergency hemodialysis rate and annual medical costs. One study reported that MDC significantly decreased end‐stage renal disease (ESRD) risk (Chen et al, 2019). Inconsistent results have been reported for other outcome indicators, including hospitalization for cardiovascular or infection events, medications use, and incidence of dialysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding secondary outcome indicators, two studies reported that MDC significantly decreased the emergency hemodialysis rate and annual medical costs. One study reported that MDC significantly decreased end‐stage renal disease (ESRD) risk (Chen et al, 2019). Inconsistent results have been reported for other outcome indicators, including hospitalization for cardiovascular or infection events, medications use, and incidence of dialysis.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies also recommend inclusion of other specialists (e.g., cardiac surgeon, urological surgeon, pharmacist, psychotherapist, and social worker). In Taiwan, MDC for stage 3–5 CKD patients includes a nephrologist, renal health education professional, and nutritionist (Chen et al, 2019; P. M. Chen et al, 2015; Chen et al, 2013). The MDC in other countries includes surgeons (cardiovascular surgeon, general surgeon) and a kidney transplant team to provide the optimal care needed to prevent or delay worsening of renal function and to improve care and quality of life for CKD patients (Fluck & Taal, 2018; Johns et al, 2015; Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management and education were dependent on the stages of CKD, according to the 2002 NKF-KDOQI guidelines 17 , and the reimbursement policies of National Health Insurance (NHI). Detailed contents of this program have been described somewhere in our previous studies 12 , 18 . In 2006, Taiwan NHI launched a pay-for-performance program with indicators including CKD management, patient education, continuous care, remission of proteinuria, and maintenance of renal function for pre-End Stage Kidney Disease (ESKD) care 19 , 20 .…”
Section: Methodsmentioning
confidence: 99%
“…It further recommends referral for VA assessment and subsequent creation when the eGFR is 15–20 mL/min/1.73 m 2 , given that it is unlikely to predict the time of dialysis initiation 11 . In past decades, multidisciplinary chronic kidney disease (CKD) care programs have emerged and resulted in more effective prescriptions, a lower renal progression rate, a decrease in temporary dialysis catheter usage, and lower medical expenses 12 16 . Under the care of such a program, later referral and regular monitoring of renal progression were more under control; this made it easier to evaluate the time of determining when to create VA and how it affected the initiation of HD without using a central venous catheter.…”
Section: Introductionmentioning
confidence: 99%